2019
DOI: 10.35940/ijeat.a3024.109119
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biofuel (Bio-Ethanol) From Fruitwaste: Banana Peels

Abstract: Bio-ethanol, a type of biofuel, is known as renewable energy source as it is derived from biomass as its raw material. Biomass can be found in abundance and sustainable i.e. sources are available continuously, unlike the currently used conventional fossil fuels where these sources are limited and depleting. In this study, biomass from fruit waste, banana peels, were utilized to produce bio-ethanol via hydrolysis and fermentation process. Banana peels, a lignocellulosic biomass, possesses compositions which fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Banana peel waste is rich in fermentable sugar and recognized as an important feedstock for the production of bioethanol [102] . However, the amount of bioethanol produced depends on the amount of fermentable sugar extracted, which in turn depends on the type of sccharification method employed [27] .…”
Section: Resultsmentioning
confidence: 99%
“…Banana peel waste is rich in fermentable sugar and recognized as an important feedstock for the production of bioethanol [102] . However, the amount of bioethanol produced depends on the amount of fermentable sugar extracted, which in turn depends on the type of sccharification method employed [27] .…”
Section: Resultsmentioning
confidence: 99%
“…The results shown in Table 5 revealed that the values showed significant variation. The production of bioethanol from banana peels using Saccharomyces cerevisiae was reported by Hamzah et al (2019) to be more efficient at acidic pH values than at alkaline pH values (Table 5). The production rate was dependent on the type of yeast cells used.…”
Section: Bioethanol Production Using Saccharomyces Cerevisiaementioning
confidence: 99%
“…The increase in global warming and waste generation due to the use of fossil fuel demands alternate sources of fuel for energy generation. The carbon intensity of biofuels is very low compared with that of fossil fuels, which is an added advantage (Hamzah et al, 2019). Bioethanol has wide acceptance among various other biofuels.…”
Section: Introductionmentioning
confidence: 99%